2004
DOI: 10.1111/j.1365-2567.2004.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation up‐regulates CD80 expression through two different mechanisms in spleen B cells, B lymphoma cells, and dendritic cells

Abstract: SUMMARYWe have previously demonstrated irradiation-induced up-regulation of CD80 expression in A20-HL B lymphoma cells by inducing expression of tumour necrosis factor-a (TNF-a) and CD154. In the present study, we investigated whether irradiation also up-regulates CD80 expression in mouse spleen B cells. Because freshly prepared spleen B cells are highly sensitive to irradiation, we employed spleen B cells stimulated with lipopolysaccharide (LPS-B cells). X-irradiation (8 Gy) followed by incubation (9-12 hr) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…These authors found that localized ionizing irradiation enhanced the generation of endogenous antigen-specific T CD8 , which corresponded with increased levels of antigen within the draining lymph node. This finding is consistent with studies showing that irradiation induces upregulation of co-stimulatory molecule expression on APCs, including DCs, leading to enhanced T cell stimulatory capacity in vitro (70, 71). In the SV11 model, irradiation was not required to trigger T CD8 against the endogenous T Ag, as TCR-IV T CD8 in both the spleen and the CLN proliferated following adoptive transfer.…”
Section: Discussionsupporting
confidence: 92%
“…These authors found that localized ionizing irradiation enhanced the generation of endogenous antigen-specific T CD8 , which corresponded with increased levels of antigen within the draining lymph node. This finding is consistent with studies showing that irradiation induces upregulation of co-stimulatory molecule expression on APCs, including DCs, leading to enhanced T cell stimulatory capacity in vitro (70, 71). In the SV11 model, irradiation was not required to trigger T CD8 against the endogenous T Ag, as TCR-IV T CD8 in both the spleen and the CLN proliferated following adoptive transfer.…”
Section: Discussionsupporting
confidence: 92%
“…2 A ). Indeed, previous reports, including ours, have demonstrated a rapid activation of DCs at the lymphopenic phase after chemotherapy and TBI, associating with significant increases in the Ag-specific responses of adoptively transferred T cells (3, 14, 18, 19, 48, 49). Paulos et al demonstrated that this rapid DC activation is attributed to the significant damage to the integrity of mucosal barriers and translocation of bacterial products (LPS; a TLR4 ligand) (3).…”
Section: Discussionsupporting
confidence: 52%
“…Irradiation and/or chemotherapy leads to activation of host cells, resulting in the release of proinflammatory cytokines, such as TNF-α, IL-1 and IL-4 [71][72][73][74], and upregulation of co-stimulatory molecules, such as CD80 [75]. In a recent study, activation markers I-A b (class II) and CD86 were upregulated on splenic DCs as early as 6 h after TBI.…”
Section: Effects Of Lymphodepleting Radiation and Chemotherapy On Apcmentioning
confidence: 99%